2018
DOI: 10.20944/preprints201810.0496.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-Term Zinc Supplementation Improves Liver Function and Decreases the Risk of Developing Hepatocellular Carcinoma

Abstract: Background and Aim: Zinc plays a pivotal role in various zinc enzymes, resulting in the maintenance of liver function. Patients with chronic liver diseases (CLDs) usually have lower concentrations of zinc, which decrease further as liver fibrosis progresses. It remains unknown whether long-term zinc supplementation improves liver function and reduces the risk of hepatocellular carcinoma (HCC) development. Patients and Methods: Two hundred sixty-seven patients with CLDs who received a zinc preparation (Zn-group… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…Recently, it was reported that hypozincemia was associated with developing HCC in hepatitis C virus‐related cirrhosis . Because the long‐term administration of zinc to patients with CLD with zinc deficiency was reported to prevent worsening of liver function and progression of hepatic fibrosis, and to reduce the risk of developing HCC, zinc supplementation with zinc acetate hydrate might not only relieve various symptoms associated with zinc deficiency, but can also improve the quality of life and prognosis in patients with CLD. We hope that the present study will be helpful for better understanding zinc deficiency associated with CLDs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that hypozincemia was associated with developing HCC in hepatitis C virus‐related cirrhosis . Because the long‐term administration of zinc to patients with CLD with zinc deficiency was reported to prevent worsening of liver function and progression of hepatic fibrosis, and to reduce the risk of developing HCC, zinc supplementation with zinc acetate hydrate might not only relieve various symptoms associated with zinc deficiency, but can also improve the quality of life and prognosis in patients with CLD. We hope that the present study will be helpful for better understanding zinc deficiency associated with CLDs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many direct‐acting antivirals (DAAs) targeting HCV have been developed and have made it possible to eradicate HCV in most patients suffering from chronic hepatitis and LC. Recent papers reported that long‐term zinc supplementation decreased the risk of hepatocarcinogenesis and zinc deficiency was improved after eradication of HCV by DAA treatment . However, future studies are required to validate these results using a larger cohort of patients with zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…1 lowever, there have been few studies evaluating the role of zinc in the development of early ALD, mechanisms of action for zinc therapy in ALD, or effects of zinc on long-term outcome. Three recent studies published only in abstract form address these critical areas [6063]. …”
Section: Zinc Deficiency and Zinc Supplementation In Human Aldmentioning
confidence: 99%
“…Serum zinc concentrations tended to predict outcome. The authors concluded that oral zinc supplementation was effective at maintaining liver function and helped to prevent HCC [63]. …”
Section: Zinc Deficiency and Zinc Supplementation In Human Aldmentioning
confidence: 99%